Agile Coaching: A Hybrid Systematic Literature Review and Bibliometric Analysis - Taufiq Risal; Darwin Lie; Fajar Rezeki Ananda Lubis (Indonesian Journal Publisher, 2025)
This paper explores the evolving role of Agile coaching, synthesizing findings from a hybrid systematic literature review (SLR) and bibliometric analysis. It investigates the competencies and challenges faced by Agile coaches in supporting successful Agile transformations at both the team and organizational levels. By reviewing 16 articles from the Scopus database, the study identifies key skills, such as leadership, mentoring, conflict resolution, and facilitation of collaboration, essential for Agile coaches. The research also discusses common challenges including resistance to change, knowledge gaps, and organizational barriers. This study contributes to the growing body of knowledge on Agile coaching by providing insights into the practical and theoretical implications of the field and offering recommendations for future research.